2019
DOI: 10.1159/000494292
|View full text |Cite
|
Sign up to set email alerts
|

Cancers Preceding Parkinson’s Disease after Adjustment for Bias in a Danish Population-Based Case-Control Study

Abstract: Cancer patients are at lower risk of developing Parkinson’s disease (PD) compared with the general population. One explanation is the negative association between smoking and PD, but PD risk is also lower for cancers not related to smoking. Another explanation is survival bias where death from cancer may act as a competing risk. We conducted a large population-based case-control study in Denmark and investigated whether cancer diagnosis reduced the risk of developing PD even after adjusting for important risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…PD patients have previously been associated with a reduced risk of cancer (20). Conversely, cancer patients have been reported to have a lower risk of developing PD, even after controlling for cancer-related lifestyle factors and correcting for survival bias (21). Recently, an inverse relationship between cancer and memory decline was reported in a large population-based cohort of Alzheimer's disease patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…PD patients have previously been associated with a reduced risk of cancer (20). Conversely, cancer patients have been reported to have a lower risk of developing PD, even after controlling for cancer-related lifestyle factors and correcting for survival bias (21). Recently, an inverse relationship between cancer and memory decline was reported in a large population-based cohort of Alzheimer's disease patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the vast number of existing cohort studies, they could become an invaluable source of useful bias parameters for the populations they were sampled from. New examples in the literature suggest that the opposite procedure might also be useful : correcting biases in case-control or cohort studies using population-based register data ( 32 , 33 ). Further, even more general approaches to combining data from several data sources with different biases have been recently formalized ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several types of melanomas are recognized, including those that arise from pre-existing moles (superficial spreading melanoma), de novo (nodular melanoma), from precursor lentigo maligna (lentigo maligna melanoma), or present under nail beds or on the palms or soles (acral lentiginous melanoma). The relationship between melanoma and PD has been studied for a long time as several epidemiological studies have demonstrated increased risk of melanoma in patients with PD although the risk of other cancers is lower than expected [19][20][21][22][23][24][25], even after correcting for confounders known to reduce the risk of PD, such as smoking [26]. Mahajan and colleagues recently conducted a single-center, nested case-control study and found that cancer, especially skin cancer, was associated with delayed onset of PD, although the clinical progression was unaffected [27].…”
Section: Melanomamentioning
confidence: 99%